2020
DOI: 10.15243/jdmlm.2020.081.2439
|View full text |Cite
|
Sign up to set email alerts
|

Effect of application of organic and inorganic fertilizer on soybean yield in lowland Vertisols

Abstract: Application of organic fertilizer can maintain and improve physical, chemical, and biological soil fertility and plant productivity. However, the use of manure requires a long time and a relatively large amount to have a positive impact on the soil and plants. In this regard, a study was carried out to evaluate the effect of the application of organic fertilizer and NPK inorganic fertilizer on soybean in lowland Vertisol. The study was conducted in lowland Vertisols in Ngawi and Madiun. The experiment used a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…A correlation was also found between the dry weight of plants with root length, stem length, number of leaves, leaf weight, leaf area, and percentage of active root nodule. Meanwhile, Kuntyastuti et al [22] reported the results showed that in the lowlands Vertisol in Ngawi, which is rich in P elements, the addition of 5 tons.ha -1 of cow dung, 3 tons.ha -1 of chicken manure, 1.5 -2.5 tons.ha -1 of SANTAP-NM1 and SANTAP-NM2 fertilizers, and 300 kg.ha -1 Phonska was not necessary. Local Results Central Java / Sinabung-1036 soybean strains reached 1.95 t ha-1.…”
Section: Resultsmentioning
confidence: 99%
“…A correlation was also found between the dry weight of plants with root length, stem length, number of leaves, leaf weight, leaf area, and percentage of active root nodule. Meanwhile, Kuntyastuti et al [22] reported the results showed that in the lowlands Vertisol in Ngawi, which is rich in P elements, the addition of 5 tons.ha -1 of cow dung, 3 tons.ha -1 of chicken manure, 1.5 -2.5 tons.ha -1 of SANTAP-NM1 and SANTAP-NM2 fertilizers, and 300 kg.ha -1 Phonska was not necessary. Local Results Central Java / Sinabung-1036 soybean strains reached 1.95 t ha-1.…”
Section: Resultsmentioning
confidence: 99%
“…Organic and inorganic fertilizers combination (semi-organic farming) also the alternative application chosen by farmers to increase crop qualities and productivity. [25] informed in the research that the vertisol (low of P elements) demanded the addition of 5 t ha −1 of cow manures, 1.5-2.5 t ha −1 of Santap NM2 fertilizer, and 0.15 t ha −1 of Phonska to increase soybean yield by 21-27% (0.42-0.55 t ha −1 ). [26] declared that composted cow manure with dose of 8 t ha −1 remarkably increased the number of pods and weights of grains in soybean that was compared to the control without manures application.…”
Section: Growth and Yields Of Edamamementioning
confidence: 99%
“…In addition, the government also continues to encourage the efficient use of fertilizers through policies related to supply and distribution, as well as prices through subsidies. Various studies [1,2] reveal that the existence of a fertilizer subsidy policy aims to encourage an increase in agricultural production.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of the study of Suryana et al (2015) [3] stated that currently there are still some problems in the distribution of subsidized fertilizers in the field. These problems include: (1) In terms of planning, the allocation of subsidized fertilizers as outlined in the Regulation of the Minister of Agriculture is much lower than the needs proposed by local governments, so that it often leads to scarcity; (2) There is a moral hazard in the field, due to the large price difference (more than 50%) between the price of subsidized fertilizer and the price of non-subsidized (commercial) fertilizer that is traded in the market; (3) Not all farmers become members of farmer groups, so that farmers' fertilizer needs are not entirely included in the proposed electronic -Definitive Plan for Group Needs (eDPFGN); and (4) Farmer data contained in the eDPFGN is generally not accurate, especially regarding data on land area and cropping patterns.…”
Section: Introductionmentioning
confidence: 99%